The Effects of Offline Alcohol Advertisement Near Bus Stops and Offline Alcohol Advertisement Regulations on Alcohol Consumption Among University Students in Groningen - Salsabila, Alisa (Integrasi Sains Media, 2023)
The European Commission has reported that the Netherlands placed first for weekly alcohol consumption of 47.3% of its population in 2019. Previous research has found how offline alcohol advertisements and offline alcohol regulations have a role in influencing alcohol consumption, especially among university students. Groningen is one of the cities in the Netherlands where one in four people is a university student. This research aims to analyze the effects of offline alcohol advertisements near bus stops, as one of the main forms of transportation for university students is the bus and the effects of offline alcohol advertisements on alcohol consumption among university students in Groningen. Offline alcohol advertisement is also categorized into three types: offline alcohol advertisement with price discounts, product advertisement, and event marketing. There has also been research on how existing offline alcohol advertisement regulations increased online advertising effectiveness. This research also did a similar experiment and saw the effect on alcohol consumption. This research used the quantitative approach, and the data was collected through questionnaires spread out to 208 university students aged 18-24 years old, currently studying in Groningen. The result showed that offline alcohol advertisements with price discounts and product advertisements near bus stops positively affected alcohol consumption among university students in Groningen. It also showed that offline alcohol advertisement regulations did not significantly affect alcohol consumption among university students in Groningen, although it surprisingly increased the online alcohol advertisement effectiveness. Therefore, it is suggested that the foundation, which is responsible for the alcohol advertisement regulations, use this data for future references of the regulations. Future research could take the sample from the Netherlands, not only in Groningen, to make it more applicable.